2013
DOI: 10.1007/s11845-013-1009-8
|View full text |Cite
|
Sign up to set email alerts
|

Modest correlation between serum neopterin levels and Gensini scores in a cohort of patients undergoing coronary angiography

Abstract: By the guidance of our results, we can confidently state that there is a correlation between serum neopterin levels and the severity and extent of CAD in stable coronary artery disease patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…Higher neopterin concentrations were presented in coronary heart disease. Ozbek C et al performed a study with 40 stable angina pectoris patients and found a positive correlation between serum neopterin and Gensini scores as in this study [13]. High levels of neopterin may be due to inflammation, a compound of endothelial dysfunction.…”
Section: Discussionsupporting
confidence: 65%
“…Higher neopterin concentrations were presented in coronary heart disease. Ozbek C et al performed a study with 40 stable angina pectoris patients and found a positive correlation between serum neopterin and Gensini scores as in this study [13]. High levels of neopterin may be due to inflammation, a compound of endothelial dysfunction.…”
Section: Discussionsupporting
confidence: 65%